Hierarchically Ordered Perovskites with High Photo‐Electronic and Environmental Stability via Nanoimprinting Guided Block Copolymer Self‐Assembly (Adv. Mater. Interfaces 16/2022). Issue 16 (3rd June 2022) - Han, Hyowon; Oh, Jin Woo; Park, Jumi; Lee, Hyeokjung; Park, Chanho; Lee, Seung Won; Lee, Kyuho; Jeon, Seungbae; Kim, Sohee; Park, Youjin; Jeong, Beomjin; Ryu, Du Yeol; et al.
Abstract : Hierarchically Ordered Perovskites Hierarchically ordered perovskites are developed by nanoimprinting‐guided self‐assembly with a block copolymer template as reported in article number 2200082 by Hyowon Han, Cheolmin Park, and co‐workers. Highly enhanced photoluminescence with environmental stability is achieved by surface passivated Mie resonance of nanopattern, combined with 10 nm‐thick ultrathin self‐assembled top skin polymer layer.